Evaluation of Pregnancy Cases Under the Age Of 18 Evaluated at Children Monitoring Center (CMC) In Trabzon - Özer, Erdal (The Bulletin of Legal Medicine, 2021)
Objective: Teenage pregnancy, also known as adolescent pregnancy, is pregnancy in a female the age of 18 and under. The proportion of teen pregnancies in our country is %8-12. Pregnancies among 10- to 19-years are adversely affect the physical, mental and psychological health of the mother and baby. Our study aims to examine the main characteristics of pregnancies under age of 18 applied Children Monitoring Center (CMC) in Trabzon. Results: Between 2015-2020, 18 adolescents found under the age of 18. There were no findings in 12 cases where internal body examination was requested, old tears observed in 3 cases, hymen was intact in 3 cases. 3 pregnancies occurred in the first trimester with criminal abortion. 3 cases were terminated with therapeutic curettage in the first trimester. Premature birth was detected in 2 cases. In 10 cases, delivery occurred at the end of term. 9 perpetrators were the lover of the victim, 5 cases covered by incest, 3 of them were cousins ​​and 2 of them were brother-in-law and rest of 4 of them were unofficial spouses. Conclusions: In Minnesota study, 40-70% of teenage mothers reported a history of sexual abuse. In our study, all of teenage mothers reported a history of sexual abuse due to the fact that our data was collected from Children Monitoring Center (CMC) Trabzon, Turkey. Teenage pregnancy are adversely affect the physical, mental and psychological health of the mother. In addition to medical and forensic support, psychosocial support should be given to teen pregnancies.